Academies and free schools in England a history and philosophy of the Gove Act - Hilton, Adrian 1964- (Routledge research in education policy and politics, 2018)
Academies and Free Schools in England argues that there is a high degree of philosophical consensus and historical continuity on the policy of 'academisation' across the main political parties in England. It attempts to make sense of what are all essentially free schools by interviewing the architects of policy and their closest advisors, analysing the extent to which they invoke historical expressions of conservatism and/or liberalism in their articulation of that convergence. The book offers a unique insight into educational policy-making during the Conservative/Liberal-Democrat coalition era (2010-2015), and an in-depth analysis of the nature of liberty as it relates to state education in England. Providing original interview transcripts of the key reformers, and new accounts of a sometimes contentious history, Hilton identifies an elite 'policy community', connected by educational background, moral-religious frameworks, life experiences and shared networks of common ideology. Academies and Free Schools in England will be vital reading to academics and researchers in the field of education and education policy. It will also be of great interest to school governors, business leaders, political philosophers and those involved and interested in free schools